The Approaches from Rural Construction Land Consolidation to Sustainable Rural Land Resource Development. Issue 1 (May 2020) - Zhang, Yiye; Zhang, Zaisheng; Sun, Xuesong
Abstract: As an important property, rural construction land is related to the fundamental interests of farmers. Since rural construction land has not been efficiently used which affected the sustainable development of rural land resources, this study constructs a theoretical model of farmers' rural construction land consolidation intention, and designs a questionnaire based on the model. Based on the data analysis, this study provides empirical test and puts forward suggestions for improving present rural construction land management policy system.